2018
DOI: 10.9734/afsj/2018/42914
|View full text |Cite
|
Sign up to set email alerts
|

Spreadability, Acceptability and Compositional Properties of Table Spreads Produced from African Pear (Dacryodes edulis) Pulp

Abstract: This work was carried out in collaboration between all authors. The first author OMA is the chief supervisor to the M.Sc. student while the second author GOW is the supporting supervisor. Both of them jointly designed the study and guided the student throughout the research process. The last author CO is the M.Sc. student who conducted the research, managed the literature searches and the statistical analysis. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
1
2
Order By: Relevance
“…However, these values were significantly (p<0.05) different from those spreads produced from P. cintrinopileatus (0.1 and 0.3% gum arabic ). These moisture values were lower when compared to the moisture content of African pear spread (62.00%) as reported by Akusu et al (2018). The low moisture values of spreads in this study may be attributed to the effect of gum and show an increased shelf life of the product.…”
Section: Changes In the Moisture Content Of Mushroom Spreads During S...contrasting
confidence: 65%
See 2 more Smart Citations
“…However, these values were significantly (p<0.05) different from those spreads produced from P. cintrinopileatus (0.1 and 0.3% gum arabic ). These moisture values were lower when compared to the moisture content of African pear spread (62.00%) as reported by Akusu et al (2018). The low moisture values of spreads in this study may be attributed to the effect of gum and show an increased shelf life of the product.…”
Section: Changes In the Moisture Content Of Mushroom Spreads During S...contrasting
confidence: 65%
“…These range of pH showed that mushroom spread is slightly acidic which will enhance its preservation and storability. These values are higher when compared to the pH of African pear spread as reported by Akusu et al (2018).…”
Section: Samplescontrasting
confidence: 50%
See 1 more Smart Citation